ROLE AND FEATURES OF LEGAL ENTITIES AT INSTITUTE OF AN INDUSTRIAL HEALTH AND SAFETY - A, Tynybekov S.; A, Aldashev S. (Farabi Journal of Social Sciences, 2019)
Abstract. The article is devoted to research the difficult institution of labor law, labor safety and protection, the role of legal entities as employees. According to Article 1 of the Constitution of the Republic of Kazakhstan accepted on August 30, 1995 the Republic of Kazakhstan is the social constitutional state, and its most valuable property are life, the rights and freedoms of the person. The right to professional safety is one of fundamental human rights whose right to work according to safety requirements and purity is fixed at the constitutional level. Standards of safety and labor protection contain in the conventional international documents, such as Universal Declaration of Human Rights of 1948, International Covenant on Economic, Social and Cultural Rights of 1966 and Commonwealth of Independent States. Besides, Conventions and the Recommendations of the International Labor Organization are also applicable to regulation of the civil and labor law of the Republic of Kazakhstan. It: "Safety and labor protection in the production environment", "About protection of workers against professional pollution, noise and vibration", "Inspection of work in the industry and trade", "About prevention of industrial accidents".